2020
DOI: 10.1088/1361-6528/aba86c
|View full text |Cite
|
Sign up to set email alerts
|

Internal quantum efficiency of AlGaN/AlN quantum dot superlattices for electron-pumped ultraviolet sources

Abstract: In this paper, we describe the growth and characterization of  530-nm-thick superlattices (100 periods) of AlxGa1-xN/AlN (0 ≤ x ≤ 0.1) Stranski-Krastanov quantum dots for application as the active region of electron-beam pumped ultraviolet lamps.Highly dense (>10 11 cm -2 ) quantum dot layers are deposited by molecular beam epitaxy, and we explore the effect of the III/V ratio during the growth process on their optical performance. The study considers structures emitting in the 244-335 nm range at room temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 53 publications
3
22
1
Order By: Relevance
“…The addition of Φ Al implies an increase of the metal/N flux ratio, (Φ Al + Φ Ga )/Φ N , during the QD deposition. In ref, we demonstrated that it is possible to grow Al x Ga 1– x N QDs ( x = 0, 0.1) with high IQE (around 50%) when keeping the metal/N ratio below 0.75. Under these conditions, the growth kinetics are dominated by Ga, whose diffusion length is larger than that of Al at the QD growth temperature.…”
Section: Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The addition of Φ Al implies an increase of the metal/N flux ratio, (Φ Al + Φ Ga )/Φ N , during the QD deposition. In ref, we demonstrated that it is possible to grow Al x Ga 1– x N QDs ( x = 0, 0.1) with high IQE (around 50%) when keeping the metal/N ratio below 0.75. Under these conditions, the growth kinetics are dominated by Ga, whose diffusion length is larger than that of Al at the QD growth temperature.…”
Section: Results and Discussionmentioning
confidence: 94%
“…An active region comprising 100 periods of QDs has a total thickness of approximately 550 nm. This thickness implies that the maximum acceleration power that can be applied for electron beam excitation is around 9 kV, as determined through Monte Carlo simulations of the electron beam penetration depth . All the characterization presented in this paper was conducted using acceleration voltages ranging from 5 to 6 kV.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technology has allowed the fabrication of ZnSebased pulsed lasers that emit up to 600 W at 535 nm [12]. There are some studies of electron beam pumped AlGaN for the implementation of UV lamps [13][14][15][16][17][18][19][20]. Wunderer et al demonstrated UV lasing from an AlGaN/GaN heterostructure containing InGaN quantum wells (QWs) under pulsed electron beam excitation at 77 K [21].…”
Section: Introductionmentioning
confidence: 99%